2020
DOI: 10.1101/2020.01.20.913210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The yeast mating-type switching endonuclease HO is a domesticated member of an unorthodox homing genetic element family

Abstract: SummaryThe mating-type switching endonuclease HO plays a central role in the natural life cycle of Saccharomyces cerevisiae, but its evolutionary origin is unknown. HO is a recent addition to yeast genomes, present in only a few genera. It resembles a degenerated intein fused to a zinc finger domain. Here we show that HO is structurally and phylogenetically related to a family of unorthodox homing … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 77 publications
(102 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, of particular interest was the homology detected for the genus Lachancea : 93.1% of genes were found to be homologous between T. delbrueckii COFT1 and species L. lanzarotensis and 92.8% with species L. thermotolerans . This proximity between Lachancea and T. delbrueckii was shown before, detailing shared traits that were mainly related with osmotolerance and ethanol resistance [ 25 , 65 ], but also remarkable similarity considering the clusters of the mating-type switching endonuclease HO genes [ 38 ]. L. thermotolerans, especially, has been associated with a strain-dependent production of a diverse range of metabolic intermediates for L-lactic acid production [ 65 , 66 ], as well as ethyl lactate [ 67 ].…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, of particular interest was the homology detected for the genus Lachancea : 93.1% of genes were found to be homologous between T. delbrueckii COFT1 and species L. lanzarotensis and 92.8% with species L. thermotolerans . This proximity between Lachancea and T. delbrueckii was shown before, detailing shared traits that were mainly related with osmotolerance and ethanol resistance [ 25 , 65 ], but also remarkable similarity considering the clusters of the mating-type switching endonuclease HO genes [ 38 ]. L. thermotolerans, especially, has been associated with a strain-dependent production of a diverse range of metabolic intermediates for L-lactic acid production [ 65 , 66 ], as well as ethyl lactate [ 67 ].…”
Section: Resultssupporting
confidence: 55%
“…Finally, the genome of SRCM101298 strain, which was added to the database in July 2017, is considerably less explored and is assembled at the contig level. Additional genomes of T. delbrueckii were recently released [ 38 ]; however, not in the timeframe of the current work.…”
Section: Introductionmentioning
confidence: 99%
“…T. globosa is a sister species to T. maleeae . We sequenced the genomes of 12 strains of T. globosa (Coughlan et al, 2020 and A.Y.C. and K.H.W., unpublished) and found that 11 of them, including the type strain CBS764 T , have no GAL genes.…”
Section: Resultsmentioning
confidence: 99%
“…Coverage was approximately 85×. All other genome sequences are from sources cited in Coughlan et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation